2020
DOI: 10.3390/molecules25204663
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Activity of Steamed Ginger Extract against Ethanol/HCl-Induced Gastric Mucosal Injury in Rats

Abstract: Ginger (Zingiber officianale), the most widely consumed species, is traditionally used as a folk medicine to treat some inflammatory diseases in China and Korea. However, the functional activity of steamed ginger extract on gastric ulcers has not been previously explored. The present study aimed to investigate antiulcer activity of steamed ginger extract (GGE03) against ethanol (EtOH)/HCl-induced gastric ulcers in a rat model. GGE03 (100 mg/kg) was orally administered for 14 days to rats before oral intubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Furthermore, we calculated the human equivalent dose for the effect of GGE03. GGE03 was found to protect against EtOH/HCL-induced rat gastric mucosal injury at concentrations of 100 to 300 mg/kg [5]. Based on our findings and others, we estimate that an amount of 400 to 1,000 mg/day GGE03 is required for a 60 kg subject as calculated by the recommended body surface area normalization method [37].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, we calculated the human equivalent dose for the effect of GGE03. GGE03 was found to protect against EtOH/HCL-induced rat gastric mucosal injury at concentrations of 100 to 300 mg/kg [5]. Based on our findings and others, we estimate that an amount of 400 to 1,000 mg/day GGE03 is required for a 60 kg subject as calculated by the recommended body surface area normalization method [37].…”
Section: Discussionsupporting
confidence: 56%
“…GGE03 was prepared as previously published [5]. Briefly, ginger was washed three times with distilled water, dried at 50°C for 30 hours, and then steamed at: 2 to 2.5 kgf/cm 2 , 97°C, for 2 hours.…”
Section: Preparation Of Steamed Ginger Extract (Gge03)mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings concluded that steamed ginger extract may exhibit antiulcer activity in a rat model by reducing acute gastric ulcers. The preventive mechanism probably comes as a result of an increase in mucosal prostaglandin E2 synthesis and gastric antioxidation capability [ 157 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a previous study reported that oxidative stress during gastric inflammation induced by ethanol stimulates lipid peroxidation, as indicated by elevated malondialdehyde (MDA) levels in gastric tissues [ 4 ]. Nuclear factor kappa B (NF-κB) activation occurs during mucosal inflammation induced by gastric ulcer disease.…”
Section: Introductionmentioning
confidence: 99%